PREVALENCE OF COCCIDIA INFECTION IN KINTAMANI BALI DOG - Maheswari, Luh Gede Winda; Dwinata, I Made; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2023)
Coccidiosis is an infectious disease of the digestive tract in dogs that can cause digestive disorders. The purpose of this study was to determine the prevalence of coccidia infection and its relationship with risk factors (age, sex, maintenance system) in Kintamani Bali Dogs. Sampling was carried out in several areas in Bali, namely Denpasar City, Gianyar Regency and Sukawana Village, Kintamani District, Bangli Regency by purposive sampling. The number of research samples was 150 faecal samples and examined using the floating method. The data obtained were analyzed by chi-square test. The results showed that from 150 samples of Kintamani Bali Dog feces examined, 5 samples were positive for Coccidia infection with a prevalence of 3.33%, 2 samples were identified as infected with Eimeria spp. 1.33% (2/150) and 3 samples infected with Isospora spp. 2% (3/150). Analysis by Chi-square test there was no significant relationship between age, sex and maintenance system on the prevalence of coccidia infection in Kintamani Bali Dogs. The owner of the Kintamani Bali Dog should pay more attention to maintenance, both from feeding, cleaning the cage and also administering protozoan drugs to reduce the prevalence of Coccidia infection.